The Circassian diaspora in Turkey : a political history - Besleney, Zeynel Abidin (London : Routledge, 2014)
'A North Caucasian ethnic group that has been largely obscured in world history as a result of their expulsion from their homeland by Tsarist Russia in the 1860s, Circassians now comprise significant communities not only in the Northwest Caucasus but also in Turkey, Syria, Jordan, Europe and the US. The Circassian Diaspora investigates how a community of impoverished migrants has evolved into a well-connected and politically active diaspora. This book explores the prominent role Circassians played during the Turco-Greek War or the'Turkish National Liberation War of 1919-1922,' and examines the changing nature of Circassians' relations with the Turkish and Russian states, as well as the new actors of Caucasian politics such as the US, the EU, and Georgia. Suggesting that the Circassian case should be studied alongside those of the Jews, Armenians and other diasporas whose formation is fundamentally tied up to a violent detachment from their homeland, and arguing that Circassian diaspora politics is not a post-Soviet phenomenon but has a history dating back to early 20th century, this book will be of interest to scholars and researchers of Diaspora Studies, History, and Politics'-- c Provided by publisher.
Keywords: Circassians -- Turkey -- History; Circassians -- Turkey -- Politics and government; Immigrants -- Turkey -- History; Circassians -- Migrations; Turkey -- Ethnic relations; Turkey -- Politics and government